Rector Marcin Poczobut on the Concept of Boarding Schools for the Impoverished Nobility in the Era of the Committee of National Education - Puchowski, Kazimierz (Senoji Lietuvos literatūra, 2021)
From the moment the Committee of National Education had taken control of educational matters, the dominant role of the exclusive private colleges (Collegia Nobilium) in the education of the noble elite was reduced. The Commission opened boarding schools for the impoverished nobility, which were extremely important for the process of democratisation of education in the institutions of the Republic of the Two Nations. This type of institution meant that the acquisition of the knowledge necessary for a future profession did not necessitate becoming a student in the service of a magnate. The education of petty poor nobility was intended to make them independent of the wealthier members of society; the aim was to train them as teachers, civil servants, and soldiers, all of which were needed by the country. Headed by the royal astronomer and rector Marcin Poczobut-Odlanicki (Martin Poczobutt, 1721–1810), the ‘Great Boarding School’ of the Principal School of the Grand Duchy of Lithuania in Vilnius was the largest boarding school financed by the Committee of National Education funds, receiving 36,700 zloty annually. Usually, there would be 70 boarders and ten directors in the Vilnius school. Impoverished young nobles were prepared to fulfil their duty as citizens of the Republic of the Two Nations. Letters requesting acceptance to the boarding school illustrate high educational aspirations of the impoverished nobility. This phenomenon deserves further research into sources.